New petrified calamitaleans from the Permian of the Parnaíba Basin, central-north Brazil, part III, with some concerns regarding anatomical features of Paleozoic petrified sphenophytes - Neregato, Rodrigo [UNESP]; Rößler, Ronny; Noll, Robert; Rohn, Rosemarie [UNESP] (Elsevier, 2021)
A new petrified calamitalean is described from the Permian Motuca Formation, Parnaíba Basin, central-north Brazil. In contrast to all other three-dimensionally preserved Brazilian species, it represents a semi-self-supporting woody plant characterized by a distinctive branch system and cellular anatomy. Arthropitys buritiranensis sp. nov. is proposed to accommodate the new material. The branch architecture is composed of at least three types of branches: (i) principal woody side branches, (ii) up to three secondary woody branches per node, scattered along the stem or the principal side branches, and (iii) 8–11 leafy twigs per whorl, at every third, rarely the second node, without secondary growth. The wood is segmented into fascicular wedges and interfascicular rays, clearly visible only within the inner wood of the stem and woody branches. The tracheid walls of the secondary xylem have exclusively scalariform pits. Ray parenchyma cells have pitted horizontal walls. The new calamitalean was part of the riparian vegetation of tree ferns, calamitaleans and gymnosperms recorded in a distal fluvial plain setting. The wood shows irregular growth interruptions and, therefore, points to a seasonally dry climate that shaped even low latitude paleofloras of tropical Pangaea.
Keywords: Arthropitys; Growth architecture; Horsetails; Parnaíba Basin; Petrified calamitaleans; Stem anatomy